2017
DOI: 10.1007/s12195-017-0486-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunotheranostic Polymersomes Modularly Assembled from Tetrablock and Diblock Copolymers with Oxidation-Responsive Fluorescence

Abstract: Introduction Intracellular delivery is a key step for many applications in medicine and for investigations into cellular function. This is particularly true for immunotherapy, which often requires controlled delivery of antigen and adjuvants to the cytoplasm of immune cells. Due to the complex responses generated by the stimulation of diverse immune cell populations, it is critical to monitor which cells are targeted during treatment. To address this issue, we have engineered an immunotheranostic polymersome d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…S18). The non-cytotoxic nature of PEG-b-PPS nanocarriers observed here is consistent with previously published studies (22,23,33,72). To ensure that cytotoxicity would not influence our ensuing cell uptake studies, we used a BCP concentration of 0.5 mg/mL.…”
Section: Uptake Of Peg-b-pps Nanocarriers By Human Mps Cellssupporting
confidence: 86%
“…S18). The non-cytotoxic nature of PEG-b-PPS nanocarriers observed here is consistent with previously published studies (22,23,33,72). To ensure that cytotoxicity would not influence our ensuing cell uptake studies, we used a BCP concentration of 0.5 mg/mL.…”
Section: Uptake Of Peg-b-pps Nanocarriers By Human Mps Cellssupporting
confidence: 86%
“…Having produced FM-based scaffolds and demonstrated their unique degradation mechanism in vitro, we aimed to investigate their ability to release MCs in vivo. While difficult to quantify, biologically relevant concentrations of reactive oxygen species (ROS) have been estimated to range from 50–100 µM 63 , and we have previously demonstrated that H 2 O 2 at as low as 5 µM can induce changes in PEG-bl-PPS nanocarrier morphology 6 . We therefore hypothesized that continuous exposure of FM-scaffolds to physiologic levels of oxidation could be sufficient to induce sustained FM-to-MC transitions in vivo following subcutaneous injection in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocarriers present a versatile means of delivering therapeutic and diagnostic agents to specific cells and tissues and have become a primary basis for theranostic strategies 1 6 . Targeted nanocarrier delivery systems are primarily administered by bolus intermittent injections and infusions, with few options available for sustained delivery 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and characterization of PPSU homopolymer. PPSU can be synthesized from the complete oxidation of poly(propylene sulfide) (PPS) 14,15 , which is known for its hydrophobic-hydrophilic transition upon oxidation [16][17][18] . However, complete oxidation of PPS had not been previously achieved, since standard oxidation of PPS generates random copolymers of poly(propylene sulfoxide)co-poly(propylene sulfone) 19 .…”
Section: Resultsmentioning
confidence: 99%